MYOPIA PREVALENCE AMONG STUDENTS DURING COVID-19 PANDEMIC. A SYSTEMATIC REVIEW AND META-ANALYSIS - Adinda Sandya Poernomo; Muhammad Bagus Fidiandra1; Eka Candra Setyawan1; Arinda Putri Auna Vanadia1; Bulqis Inas Sakinah1; Lilik Djuari; Savitri, Natasha Hana (Journal of Community Medicine and Public Health Research, 2022)
The lockdown policy was implemented during the Covid-19 pandemic to stop its spread. Indonesia modified the lockdown into PSBB (Pembatasan Sosial Berskala Besar). During PSBB school activities were replaced with online learning methods. This increased screen time and near-sighted activities and reduced time outdoors, were the risk factors for myopia. The objective of this study was to determine the myopia prevalence among students during the pandemic. This study used a systematic review method with meta-analysis. Data collection was taken from PubMed, Mendeley, and Google Scholar databases published in 2020-2021. The inclusion criterion was research on myopia prevalence among students during the pandemic of Covid-19. Data retrieval used the PICO method and journal adjustments were selected using the PRISMA algorithm. Data analysis was performed using a random-effects model. Out of 971 studies found, only six studies met the criterion. The results of the study based on the forest plot showed high heterogeneity and significant differences in the results. This was probably due to the inclusion criterion being too broad. In the funnel plot, there was a possible publication bias because the data obtained was only available and accessible. Overall, the journals studied stated that increased screen time and lack of outdoor activity increased myopia prevalence. Other risk factors that consistently cause an increase in myopia prevalence are education level, paternal and maternal myopia, and too-close reading distance. Otherwise, age, gender, BMI, eye exercise, eating habits, posture, and lighting while reading showed so many differences in the results that conclusions cannot be made.